Policy Analysis of The CIPP Model in Eradication of Illiteracy Towards Food Security in the Baduy Community of Lebak Regency - Harits Hijrah Wicaksana; Hendy Tannady (Greenation Research & Yayasan Global Resarch National, 2026)
Iliteracy eradication is positioned as a strategic instrument for human development, but its implementation in indigenous communities presents a policy dilemma between formal education interventions and protecting local socio-cultural systems. This study aims to analyze the CIPP model policy in alleviating illiteracy towards food security in the Baduy indigenous community. A qualitative approach was used using in-depth interviews, observations, and documentation studies of regional policies. The analysis was conducted thematically through four CIPP dimensions: Context, Input, Process, and Product. In the context dimension, illiteracy eradication remains a regional development agenda, but is not universally established due to the recognition of the uniqueness of the Inner Baduy custom. In the input dimension, regulations, budget support, and institutional structures are available, but have not been designed within an integrative framework that links literacy to strengthening the local food security system. In the process dimension, policy implementation shows an adaptive and restrictive pattern, where external intervention is limited to maintain social stability and customary sustainability. In the product dimension, the Baduy indigenous community's food security is relatively well maintained through a system of huma agriculture and leuit management based on pikukuh karuhun, although formal literacy is not internalized. This study concludes that there is a disconnect between administrative literacy indicators and the socio-ecological literacy practices of indigenous communities. Therefore, it is necessary to formulate contextual literacy policies that align with local food security systems and value structures to achieve inclusive and sustainable development.